The Effect of Flipped Classroom Strategy On Learning Volleyball Serving and Receiving In Second Grade Secondary School Students - Lagta, Sameer; Hassan, Muhammed (Journal of Physical Education, 2019)
The research aim at using flipped classroom strategy in learning volleyball skills. The researchers used the experimental method on second grade students from Seda Al Marifa secondary school divided into two equal groups (10) controlling group, and (10) experimental group. The main experiment was applied from 24/2 – 21/4/2019 with two teaching sessions per week for eight weeks. The data was collected and treated using proper statistical operations to conclude that flipped classroom have a positive effect in learning volleyball serving and receiving skills, the prepared video clips have a clear effect on creating suspense a matter that affected their learning level. Finally the researchers recommended activating flipped classroom strategy use by physical educators in schools due to their positive role in learning fundamental skills in volleyball as well as making similar studies using the same strategy on other variables.